Q. 1 A3.7( 24 Votes )

For each of the f

Answer :

Sum of the zeroes = - 8/3


Product of the zeroes = 4/3


P(x) = x2 - (sum of the zeroes) + (product of the zeroes)


= x2 - 8x/3 + 4/3


= 3x2 - 8x + 4


By splitting the middle term


3x2 - 8x + 4 = 0


3x2 - (6x + 2x) + 4 = 0


3x2 - 6x - 2x + 4 = 0


3x(x - 2) - 2(x - 2) = 0


(x - 2)(3x - 2) = 0


x = 2, 2/3


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses